Pengaruh Citra Merek Terhadap Loyalitas Perguruan Tinggi Melalui Social Media Customer Engagement dan Kepuasan Pelanggan - Darmadi, Roby; Silitonga, Parlagutan; Kristiadi, Al Agus (Universitas muhammadiyah palembang, 2021)
This study aims to analyze the influence of brand image on the brand loyalty of private universities mediated by social media customer engagement and customer satisfaction. This research is a quantitative research using nonprobability sampling. 218 students and alumni of a tourism college in Jakarta were used as respondents to fill out the questionnaire. The data analysis method used is Structural Equation Model (SEM). The results revealed that brand image directly has a significant effect on brand loyalty. Social media customer engagement and customer satisfaction are indirect mediators that significantly affect brand image to brand loyalty.